PENGARUH RASIO CAR, NPL, NIM DAN GWM TERHADAP LABA BANK GO PUBLIC TAHUN 2005-2007 - Anggreni, Kartika; Ika, Paskah (Jurnal Analisis Bisnis Ekonomi, 2008)
Financial ratios are useful measures for explaining the future earning changes. In this research, there are four financial ratios comprise in four categories is used for explaining future earning changes. The objective of this research is to empirically examine whether financial ratios CAR, NPL, NIM dan GWM have ability for explaining future earning changes on banks go public period 2005-2007.This research is an improvement of Zainuddin and Hartono (1999). Sample used in this research are 52 banks go public period 2005-2007 listed in Bursa Efek Indonesia (BEI). There are two variables daa that are used in this research, independent variable and dependent variable. Independent cvariable data are CAR, NPL, NIM and GWM ratios. While, dependent variable data is future earning changes of the banks go public. The variables patterened in this research are tested using multiple regression method and include normality test, auto correlation test, heteroscedasticity test and multicolleniarity test. The result of his research show that CAR, NPL, NIM and GWM ratios does not have a significant influence on future earning changes of banks go public period 2005-2007. While partial, NPL just the ratio that has a significant influence on future earning changes of banks go public period 2005-2007.